Hermeneutics a very short introduction - Zimmermann, Jens 1965- (Very short introductions, 2015)
Hermeneutics is the branch of knowledge that deals with interpretation, a behaviour that is intrinsic to our daily lives. As humans, we decipher the meaning of newspaper articles, books, legal matters, religious texts, political speeches, emails, and even dinner conversations every day. But how is knowledge mediated through these forms? What constitutes the process of interpretation? And how do we draw meaning from the world around us so that we might understand ourposition in it? Jens Zimmerman traces the history of hermeneutic theory, setting out its key elements, and demonstrating how they can be applied to a broad range of disciplines: theology; literature; law; and natural and social sciences